2019
DOI: 10.1097/md.0000000000015995
|View full text |Cite
|
Sign up to set email alerts
|

The TrueCPR device in the process of teaching cardiopulmonary resuscitation

Abstract: Background: International resuscitation guidelines emphasize the importance of high quality chest compressions, including correct chest compression depth and rate and complete chest recoil. The aim of the study was to assess the role of the TrueCPR device in the process of teaching cardiopulmonary resuscitation in nursing students. Methods: A prospective randomized experimental study was performed among 94 first year students of nursing. On the next day, the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
7

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 41 publications
1
30
0
7
Order By: Relevance
“…Many studies indicate that the use of CPR feedback devices can improve chest compression quality [32][33][34][35]. Buléon et al [17] demonstrated that a real-time feedback device provided longer, effective, steadier chest compressions over time; however, as the presented study has revealed, the depth parameters of chest compressions using the device were higher than those of manual compressions, but still insufficient in relation to the current CPR guidelines [19,36].…”
Section: Discussionmentioning
confidence: 78%
“…Many studies indicate that the use of CPR feedback devices can improve chest compression quality [32][33][34][35]. Buléon et al [17] demonstrated that a real-time feedback device provided longer, effective, steadier chest compressions over time; however, as the presented study has revealed, the depth parameters of chest compressions using the device were higher than those of manual compressions, but still insufficient in relation to the current CPR guidelines [19,36].…”
Section: Discussionmentioning
confidence: 78%
“…Training. We identified 5 RCTs 324,327,329,331,332 that addressed this outcome. We identified low-certainty evidence (downgraded for risk of bias and indirectness) from 4 RCTs that used true feedback devices.…”
Section: Cpr Performance From Training Conclusion To 1 Year Aftermentioning
confidence: 99%
“…We identified low-certainty evidence (downgraded for risk of bias and indirectness) from 4 RCTs that used true feedback devices. 324,327,329,331 All of these studies were in laypeople or junior healthcare providers, and they reported improvements in retention of CPR skills at 7 days to 3 months after training.…”
Section: Cpr Performance From Training Conclusion To 1 Year Aftermentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, where an absence of stem reflexes cannot be established, the irreversible cardiac arrest shall be established based on the conditions described in the first situation [11]. Thanks to the development of medical technologies over the last decades and the increasing availability of modern devices in both pre-hospital and in-hospital settings, there are techniques for determining the quality of resuscitation [14,15] and the return of spontaneous circulation [16]. Current guidelines for cardiopulmonary resuscitation published by the European Resuscitation Council [17,18] and the American Heart Association [19,20] recommend that capnography should be used during CPR as a method to assess the correctness of airway management and ventilation.…”
Section: Criteria For the Diagnosis Of Irreversible Cardiac Arrestmentioning
confidence: 99%